PENGARUH KEKAYAAN DAERAH, TINGKAT KESEJAHTERAAN MASYARAKAT, DAN KUALITAS LAPORAN KEUANGAN TERHADAP INTERNET FINANCIAL REPORTING - Mega Melati; Dian Fitria Handayani (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2021)
This study aims to determine of the effect of regional wealth, level of public welfare, and quality of financial reports on Internet Financial Reporting (IFR) for Regency/City Governments on the island of Sumatera in the 2019 fiscal year. Internet Financial Reporting in this study was measured based on the availability of financial information in accordance with the Instruction of the Minister of Home Affair No. 188.52/1797/SJ 2012. This study used a purposive sampling technique, the sample in this study includes 130. Financial reports data and GRDP/per capita income were obtained through the official website of the BPK and BPS, while the IFR data was obtained through the website of each local government for the year 2019 and processed by multiple linear regression using SPSS. The results show that regional wealth has a significant positive effect on the implementation of Internet Financial Reporting. While the level of community welfare and quality of financial reports do not have effect on the implementation of Internet Financial Reporting. This paper gives a comprehensive literature survey on the effect of the regional wealth, level of public welfare, and quality of financial reports on the Internet Financial Reporting in regional government on the Island of Sumatera.Keywords: Community Welfare, Internet Financial Reporting, Local Government, Regional Wealth, Quality of Financial Reports ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh kekayaan daerah, tingkat kesejahteraan masyarakat, dan kualitas laporan keuangan terhadap Internet Financial Reporting (IFR) Pemerintah Kabupaten/Kota di Pulau Sumatera Tahun Anggaran 2019. Pelaporan Keuangan Internet dalam penelitian ini diukur berdasarkan ketersediaan informasi keuangan sesuai dengan Instruksi Menteri Dalam Negeri Nomor 188.52/1797/SJ 2012. Penelitian ini menggunakan teknik purposive sampling, sampel dalam penelitian ini berjumlah 130 orang. Data laporan keuangan dan PDRB/pendapatan per kapita diperoleh melalui website resmi BPK dan BPS, sedangkan data IFR diperoleh melalui website masing-masing pemerintah daerah selama tahun 2019 dan diolah dengan regresi linier berganda menggunakan SPSS. Hasil penelitian menunjukkan bahwa kekayaan daerah berpengaruh positif terhadap penerapan Internet Financial Reporting. Sedangkan tingkat kesejahteraan masyarakat dan kualitas laporan keuangan tidak berpengaruh terhadap implementasi Internet Financial Reporting. Tulisan ini memberikan kajian literatur yang komprehensif tentang pengaruh kekayaan daerah, tingkat kesejahteraan masyarakat, dan kualitas laporan keuangan terhadap Internet Financial Reporting pada pemerintah daerah di Pulau Sumatera.Kata Kunci: Kekayaan Daerah, Kesejahteraan Masyarakat, Kualitas Laporan Keuangan, Pelaporan Keuangan Internet, Pemerintah Daerah